1998
DOI: 10.1038/bjc.1998.628
|View full text |Cite
|
Sign up to set email alerts
|

Fatal bleomycin pulmonary toxicity in the west of Scotland 1991-95: a review of patients with germ cell tumours

Abstract: Summary We conducted a retrospective review of fatal bleomycin pulmonary toxicity in patients treated for germ cell tumours dunng 1991-95 at the Beatson Oncology Centre, Glasgow. Case notes of patients treated with bleomycin were reviewed with respect to cumulative bleomycin dose, renal impairment, exposure to supplemental oxygen, thoracic radiotherapy and age. A total of 194 patients underwent chemotherapy, of whom 180 received bleomycin-containing regimens. Five fatal cases of pulmonary toxicity were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
68
3
5

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(83 citation statements)
references
References 19 publications
6
68
3
5
Order By: Relevance
“…Some studies have reported increased bleomycin-related toxicity in older patients with testicular GCC, 15,16 and 1 report even suggested that bleomycin should not be used routinely in patients aged 40 years who have testicular GCC because of an increased risk of bleomycin-induced pulmonary toxicity. 17 However, this was not supported by the current study, in which the majority of patients aged 40 years tolerated full doses of bleomycin if their lung function was monitored carefully. Although the difference was not significant, there was a trend toward higher GCC mortality in patients aged 40 years who received reduced doses of bleomycin in the current study, in agreement with previous studies, which demonstrated that bleomycin was an important part of GCC treatment, because both disease-free and overall survival were superior when bleomycin was part of the treatment.…”
Section: Discussioncontrasting
confidence: 42%
“…Some studies have reported increased bleomycin-related toxicity in older patients with testicular GCC, 15,16 and 1 report even suggested that bleomycin should not be used routinely in patients aged 40 years who have testicular GCC because of an increased risk of bleomycin-induced pulmonary toxicity. 17 However, this was not supported by the current study, in which the majority of patients aged 40 years tolerated full doses of bleomycin if their lung function was monitored carefully. Although the difference was not significant, there was a trend toward higher GCC mortality in patients aged 40 years who received reduced doses of bleomycin in the current study, in agreement with previous studies, which demonstrated that bleomycin was an important part of GCC treatment, because both disease-free and overall survival were superior when bleomycin was part of the treatment.…”
Section: Discussioncontrasting
confidence: 42%
“…This type of pulmonary toxicity has extensively been studied and attributed to a majority of the pulmonotoxic antineoplastic agents, of which bleomycin is the prototype and nitrosoureas rank second [3][4][5][6][7]. Major concern with this pulmonary toxicity is the potential to progress to irreversible chronic pulmonary fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…7C), suggesting that BLH is not participating in bleomycin action in lung cells. According to the clinical reports, up to 46% of patients will develop pneumonitis and mortality rate is approximately 3% after administration of bleomycin (21,22), showing individual differences. Therefore, lower level of BLH is not a unique factor to determine the bleomycin-induced pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%